An Automatic Sliding Doors Using RFID and Arduino - 1 (International Journal of Artificial Intelligence & Robotics (IJAIR), 2020)
The door is an important component in a building as security. It is used as access in and out of a room. People in the modern era now want everyday life that is completely automated, so that the work can be done easily without wasting energy and can shorten the time. Along with the rapid development, the need for effectiveness and efficiency is prioritized in various fields. The purpose of this paper is to design an automatic sliding door that only detects one Radio Frequency Identification (RFID) card to open and close. The use of RFID systems can strengthen the security level of building access. This study uses a data processing method in the form of an ID number generated from a tag. Specifications in the discussion of the results in this study include a motor that uses a 12-volt DC motor, a maximum door weight of 5 kg, can only detect one RFID to open and close the door, and the sliding door used is one door. The results of system testing are obtained to open a door that is without load, and the door can move 14 cm from the distance of the door hole so that it opens. Doors with a load of 1-1.5 kg also move 14 cm from the distance of the door opening when open. Doors with a load of 2-3 kg only move 12.5-9.5 cm from the distance of the door so that it opens. When the door gets heavier 3.5-4 kg, the door moves only 7.5-3 cm from the distance the door hole remains closed.